PENGARUH E-COMMERCE UNTUK UMKM DAN PENGEMBANG EKONOMI DI INDONESIA - Muhammad Reffy Fadilah; Dian Sudianti; Ernita Shafa Nur Fadhillah; Rizka Nurul Hanifah; Mutia Zubaidah (LP2M Universitas Bina Bangsa, 2023)
The purpose of this research is to ascertain how e-commerce has affected Indonesian MSMEs and Economic Growth. This research uses qualitative methods and classified as descriptive research. The method used in this research is document or text study. Research uses data analysis in this work, especially data reduction, data presentation and verification or data findings